O preenchimento de lacunas de aspecto verbal em teste cloze: pistas de compreensão em leitura - Santos, Gislane Evangelista dos (2025)
Reading is comprehension (Morais, Leite, Kolinski, 2013). For a deep understanding of a text, the reader must construct a situational model that represents the described situation, which occurs through the processing of the text base at the linguistic levels of microstructure and macrostructure (Perfetti; Landi; Oakhill, 2013; van Dijk; Kintsch, 1983; Kintsch; Rawson, 2013). In narrative texts, the verb and its categories—tense, aspect, and modality—act as textual coherence mechanisms and form the structure of discourse planes: foreground and background. In particular, aspect is responsible for distinguishing these planes, with punctual verbs being characteristic of the foreground, while durative verbs predominantly occur in the background (Givón, 2011; 1993; Hopper, 1979; Travaglia, 2014). This study aimed to investigate how aspectual and inflectional divergences in readers' responses, when filling in verb gaps in narratives, interfere with comprehension and what cues they reveal about this process. To achieve this, we collected reading data from final-year elementary school students at the Colégio de Aplicação of the Federal University of Sergipe (CODAP-UFS) through three reading task applications throughout the academic year. Focusing on the verb class, we explored the Cloze Test considering different gap-filling possibilities. In addition to the traditional test with random gaps, we designed two additional formats: blank gaps (Sadeghi, 2014) and forcedchoice. Focusing on divergent responses, we analyzed the results based on the theoretical reading model (Kintsch, 2005; Kintsch; Rawson, 2013; Perfetti, 1999; van Dijk; Kintsch, 1983) and perspectives that address verbs as grammatical mechanisms of coherence in narrative (Givón, 2011; 1993; Hopper, 1979). We observed a tendency for students to choose durative actions over punctual aspects. Since the function of the punctual aspect is to ensure temporal progression, this type of response suggests constraints in successfully forming a mental image of the narrated situation. Likewise, inaccuracies in the use of verb forms impact comprehension processes due to disruptions in the temporal sequence, indicating limitations in morphological knowledge and syntactic analysis. Blank gaps also provide clues to comprehension difficulties, as the absence of a response to the gap hinders information integration and, consequently, reading fluency. This suggests that the reader has not yet processed the syntactic elements within the sentence in which the verb is inserted, indicating a reading process still restricted to word-by-word identification without advancing to more complex levels of meaning construction. Beyond expanding the existing literature on verbal aspect in comprehensionoriented applications, this study contributes to reading instruction. We argue that addressing the function of the verb in narrative dimensions allows educators to identify specific comprehension difficulties in this type of text and implement targeted interventions. Thus, grammar teaching is integrated with reading instruction.